2020
DOI: 10.1186/s41927-019-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the pathway to psoriatic arthritis diagnosis: results from a web-based survey of patients in the United States

Abstract: Background: There are limited real-world data on the diagnostic experiences of patients with psoriatic arthritis (PsA), including medical care sought and potential barriers to diagnosis. We aim to describe patient experiences related to receiving a PsA diagnosis. Methods: Ours was a mixed-method, 2-phase study. Phase 1 comprised concept elicitation and cognitive interviews with clinical experts and adults diagnosed with PsA to develop a cross sectional, web-based survey. US adults with a self-reported PsA diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
(36 reference statements)
0
24
1
Order By: Relevance
“…Similarly, delay could be related to provider misattribution of PsA signs or symptoms to more common conditions, such as trauma, overuse, degenerative disease, fibromyalgia, or gout. In a US patient survey, less recognized symptoms of PsA, such as enthesitis and back pain, were also associated with diagnostic delay (19). Inflammatory back pain symptoms were not different between patients with and without diagnostic delay in our study.…”
Section: Discussioncontrasting
confidence: 39%
“…Similarly, delay could be related to provider misattribution of PsA signs or symptoms to more common conditions, such as trauma, overuse, degenerative disease, fibromyalgia, or gout. In a US patient survey, less recognized symptoms of PsA, such as enthesitis and back pain, were also associated with diagnostic delay (19). Inflammatory back pain symptoms were not different between patients with and without diagnostic delay in our study.…”
Section: Discussioncontrasting
confidence: 39%
“…Diagnostic delays may in turn lead to serious health consequences—a study by Harron et al showed that the diagnostic delay of even 6 months can lead to significantly more radiographic damage and worse physical function [ 21 ]. In order to ensure early detection of the disease, it seems crucial to promptly refer a patient with a suspected PsA to a rheumatologist as distinguishing PsA from other joint diseases may be challenging for a non-rheumatologist [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nature of PsA symptoms at early stages can often be misattributed to psychological distress rather than somatic illness, which leads to clinical inertia and progression of untreated disease, further exacerbating concerns over somatic manifestations. It has been observed that misdiagnoses, of which psychosomatic disorders represent over one fourth, are associated with delays in diagnosis [ 4 ]. Nontreatment and undertreatment have been reported for a large proportion of patients, with patient dissatisfaction over therapy remaining prevalent, suggesting that important patient domains are not adequately improved, while physicians may not be inclined to initiate or intensify treatment [ 10 , 11 ].…”
Section: Psychosocial Aspects and Quality Of Life In Psoriatic Artmentioning
confidence: 99%
“…PsA is preceded by a preclinical phase with nonspecific musculoskeletal symptoms (e.g., pain, stiffness, joint tenderness), though not all patients with psoriasis will develop PsA, nor is family history of disease a deciding factor. Delays in the route to PsA diagnosis can commonly occur over several months [ 4 ], which can lead to mental distress and patient dissatisfaction (see Figure 1 ). Symptoms related to arthralgia (pain, stiffness, tenderness) or evidence of subclinical synovitis may confer a higher risk for developing PsA [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%